2018
DOI: 10.1111/sms.13229
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to guide classification of para swimmers with limb deficiency

Abstract: The International Paralympic Committee has directed International Federations that govern Para sports to develop evidence-based classification systems. This study defined the impact of limb deficiency impairment on 100 m freestyle performance to guide an evidence-based classification system in Para Swimming, which will be implemented following the 2020 Tokyo Paralympic games. Impairment data and competitive race performances of 90 international swimmers with limb deficiency were collected. Ensemble partial lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…It appears these swimmers have reduced limb length and surface area that predominately impacts their ability to generate propulsive forces during swimming, rather than causing increased active or passive drag. 23 Comparatively, there were lower coefficients of determination reported for Para swimmers with impaired muscle power (adj. R 2 = .63 to .70, p < .001) and hypertonia (adj.…”
Section: Discussionmentioning
confidence: 93%
“…It appears these swimmers have reduced limb length and surface area that predominately impacts their ability to generate propulsive forces during swimming, rather than causing increased active or passive drag. 23 Comparatively, there were lower coefficients of determination reported for Para swimmers with impaired muscle power (adj. R 2 = .63 to .70, p < .001) and hypertonia (adj.…”
Section: Discussionmentioning
confidence: 93%
“…In sport, DSS have been used for purposes such as scheduling optimization (S. Robertson & Joyce, 2018;S. J. Robertson & Joyce, 2015), sport-modality classification (Hogarth, Payton, Van de Vliet, Connick, & Burkett, 2018), skill/movement evaluation and classification (Clermont, Osis, Phinyomark, & Ferber, 2017;Kovalchik & Reid, 2018;Novatchkov & Baca, 2013;Pernek, Kurillo, Stiglic, & Bajcsy, 2015;Richter, King, Falvey, & Franklyn-Miller, 2018;Rindal, Seeberg, Tjonnas, Haugnes, & Sandbakk, 2017;Whiteside, Cant, Connolly, & Reid, 2017;Woods, Veale, Fransen, Robertson, & Collier, 2018;Wundersitz et al, 2015), assessing decision-making and motor control (Maselli et al, 2017), talent identification and team selection (M. Lai, Meo, Schifanella, & Sulis, 2018;B Ofoghi, Zeleznikow, Macmahon, & Dwyer, 2013;Taha, Musa, Abdul Majeed, Alim, & Abdullah, 2018;Woods et al, 2018;Xie, Xu, Nie, & Nie, 2017), biomechanical analysis (Bertani, Cappello, Benedetti, Simoncini, & Catani, 1999;Ertelt, Solomonovs, & Gronwald, 2018;Kianifar, Lee, Raina, & Kulic, 2016;Kipp, Giordanelli, & Geiser, 2018;Richter et al, 2018), assessing injury risk (Carey et al, 2018;Li, Huang, Wang, Yu, & Ao, 2016;Lopez-Valenciano et al, 2018;Rossi et al, 2018;Ruddy et al, 2018;Thornton, Delaney, Duthie, & Dascombe, 2017) & Robertson, 2017;Jaspers et al, 2018;Nagata et al, 2016), or assessing fatigue…”
Section: Decision Support Systems In Sporting Organizationsmentioning
confidence: 99%
“…While some studies demonstrated the impact of the impairment on swimming performance 4 and race pace strategies, 5 others tested and proposed the implementation of quantitative measures and new methods into the classification process. 4,69 Regarding the physical impairment classification, Oh et al. 6 analyzed the normalized passive drag and verified an inconsistent difference between adjacent classes, and high within-class variability in the lower ones.…”
Section: Introductionmentioning
confidence: 99%
“…Hogarth et al. 7 investigated the impact of limb impairment on 100 m freestyle performance and provided insights to improve the definition of athletes’ classes through anthropometric parameters. Finally, Hogarth et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation